Helping skills facilitating exploration, insight, and action - Hill, Clara E. 1948-; O'Brien, Karen M. (Washington, DC American Psychological Association, 1999)
This book presents a three-stage model of helping, grounded in 25 years of research, that can be used to assist individuals who are struggling with emotional or transitional difficulties. To master the skills they need to lead clients through the Exploration, Insight, and Action stages, students are given both theoretical guidance and opportunities for formulating solutions to hypothetical clinical problems. Grounded in client-centered, psychoanalytic, and cognitive-behavioral theory, this book offers an integrative approach. Tables and lists supplement the text, along with clinical examples.--From publisher's description.
Overview. Becoming an effective helper -- Theoretical foundation of the three-stage model of helping -- Process of helping -- Ethical issues in helping -- Exploration stage. Overview of the exploration stage -- Attending and listening -- Restatement -- Open question -- Reflection of feelings -- Additional skills for the exploration stage -- Integrating the skills of the exploration stage -- Insight stage. Overview of the insight stage -- Challenge -- Interpretation -- Self-disclosure -- Immediacy -- Integrating the skills of the insight stage -- Action stage. Overview of the action stage -- Information -- Direct guidance -- Integrating the skills of the action stage -- Final thoughts. Putting it all together.
Includes bibliographical references (pages 347-362) and indexes.
Keywords: Counseling -- Textbooks; Helping behavior -- Textbooks